PENGERMPUKAN DAGING DENGAN ENZIM PROTEASE TANAMAN BIDURI (Calotropis gigantea) (Meat Tenderization using Protease of Biduri Plant (Calotropis gigantean)) - Erni Sofia Murtini; . Qomarudin (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Tenderness is the main attribute of meat, wich influences consumer acceptability. Protease enzyme(like papain, bromelin and ficin) are known to be used for improving tenderness of meat trough degredation of the protein. Biduri plant (Ccalotropis gigantea) contains protease enzyme in its latex or the young tissue (0-20 cm plant tip). After isolation of crude enzyme using ammonium sulphate, the enzyme was the applied to tenderise meat at concentrations 0; 0.25; 0.5; 0.75 and 1.0%. The result showed that concentration of protease enzyme affected to meat tenderness that determined by compression test and tensile strenght. The enzyme (0.5%) was enough to tenderise meat indicated by descreasing its compression test value to 201, 160 N 9 from control of 228,582 N) and tensile stenght value to 4.618 N (from control 9.588 N)